2017
DOI: 10.1016/j.bbmt.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Clinical Findings and Plasma Biomarkers after Fourteen Days of Prednisone Treatment for Acute Graft-versus-host Disease

Abstract: We examined the hypothesis that plasma biomarkers and concomitant clinical findings after initial glucocorticoid therapy can accurately predict failure of graft-versus-host-disease treatment and mortality. We analyzed plasma samples and clinical data in 165 patients after 14 days of glucocorticoid therapy and used logistic regression and areas under receiver-operating characteristic curves (AUC) to evaluate associations with treatment failure and non-relapse mortality (NRM). Initial treatment of GVHD was unsuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…High ST2 and Regenerating islet-derived 3-α (REG3α) when monitored as early as 1 week after the initiation of treatment determined the non-responder rates (64). Similar findings were reported with the combination of ST2 and T-cell immunoglobulin mucin-3 (TIM3) at 14 days post initiation of prednisone (64,65).…”
Section: Systemic Biomarkerssupporting
confidence: 57%
“…High ST2 and Regenerating islet-derived 3-α (REG3α) when monitored as early as 1 week after the initiation of treatment determined the non-responder rates (64). Similar findings were reported with the combination of ST2 and T-cell immunoglobulin mucin-3 (TIM3) at 14 days post initiation of prednisone (64,65).…”
Section: Systemic Biomarkerssupporting
confidence: 57%
“…53 However, the majority of the other biomarkers discovered so far do correlate with clinical data; or (2) response to treatment, 53,67,[69][70][71] but can also be used as potential response measures to adapt the treatment. 98 Currently, there are no "preemptive intervention" clinical trials using biomarkers measured prior to clinical manifestation of GVHD. Although a schema for a preemptive trial to decrease the aGVHD incidence using biomarkers has been reported, 96,97 cGVHD biomarkers still lack the sensitivity and specificity required for clinical trial use.…”
Section: Incorporating Posttransplantation Biomarkers In Clinical Trialsmentioning
confidence: 99%
“…38,39 A link between endothelial injury and GVHD is supported by a number of recent studies. [40][41][42][43][44] The ability to predict response to GVHD therapy using suppressor of tumorigenicity 2 (ST2) as a biomarker has been reproducibly demonstrated. 22,23 In addition, a connection between endothelial injury and release of soluble ST2 has been proposed and is supported by evidence from other inflammatory states like systemic scleroderma and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%